Experimental and Theoretical Studies on Flexural Performance of Stainless Steel Reinforced Concrete Beams - Qingfu Li; Wei Guo; Chenhui Liu; Yihang Kuang; Huitao Geng (Advances in Civil Engineering)
In this paper, the flexural characteristics of stainless steel (SS) reinforced concrete beams are studied and analyzed. We mainly focus on their crack mode, failure mode, load-deflection curve, and bearing capacity. Six beams with test parameters, including the diameter of reinforcement, the type of the reinforcement, and the stirrup spacing, were tested in 4-point bending. The test results indicate that the failure mode of SS reinforced concrete beam can be divided into three stages: elastic stage, cracking stage, and failure stage. The midspan section deformation of SS reinforced concrete beam conforms to the assumption of plane section. Under the same reinforcement condition, the normal section and the oblique section bearing capacities of the SS reinforced concrete beams are significantly higher than those of the ordinary reinforced concrete beams. In addition, the prediction of cracking moment and bearing capacity calculated by ACI 318-14 and GB 50010-2010 was also evaluated. The calculation results of the two codes were safe and conservative, and GB 50010-2010 provided more accurate prediction of cracking moments. Furthermore, to verify the reliability of the test results, finite element models were established and the analytical results corroborated well with the test results.